Answer:
A (1, −2) → A ′(−4, −1) → A ″(−1, −1)
Step-by-step explanation:
Use the first translation vector <−5, 1> to determine the rule for translation of the coordinates: (x, y)→(x+(−5), y+1).
Apply the rule to translate point A(1,−2).
A(1,−2)→(1+(−5),−2+1)→A'(−4,−1).
Then use the second translation vector <3, 0> to determine the rule for translation of the coordinates: (x, y)→(x+3, y+0).
Apply the rule to translate point A'(−4,−1).
A'(−4,−1)→(−4+3,−1+0)→A''(−1,−1).
Therefore, A(1,−2)→A'(−4,−1)→A''(−1,−1) represents the translation of A(1,−2) along the vector <−5, 1> and then the vector <3, 0> .